2023
DOI: 10.1097/md.0000000000033793
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and practices (KAP) during the malaria elimination phase: A household-based cross-sectional survey

Siddig Ibrahim Abdelwahab,
Ibrahim M. Elhassan,
Osama Albasheer
et al.

Abstract: Malaria is a major health problem in Southwestern Saudi Arabia. This study aimed to measure the level of community understanding of malaria transmission, protection, and treatment. A questionnaire-based cross-sectional study enrolled 1070 participants from 2 districts with different malaria prevalence rates in Jazan Province. The response rate was 97.27%. Of the 1070 total; 754 (70.5%) had heard about malaria. Sixty-seven percentage know that fever was the main symptom. Approximately 59.8% did not know that st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Furthermore, this study revealed a striking fact: 26 out of 27 breeding sites were human-made, aligning with previous research showing that human-constructed larval habitats often outnumber natural ones (28). This predominance of human-made breeding sites emphasizes the critical role of human involvement in mosquito control efforts, as highlighted by earlier research (29). Increasing public awareness and participation in breeding site control is crucial to reduce the prevalence of mosquito-borne diseases.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, this study revealed a striking fact: 26 out of 27 breeding sites were human-made, aligning with previous research showing that human-constructed larval habitats often outnumber natural ones (28). This predominance of human-made breeding sites emphasizes the critical role of human involvement in mosquito control efforts, as highlighted by earlier research (29). Increasing public awareness and participation in breeding site control is crucial to reduce the prevalence of mosquito-borne diseases.…”
Section: Discussionsupporting
confidence: 88%
“…This region is known to have a high prevalence of diseases such as leishmaniasis and Rift Valley fever. [ 11 , 13 , 14 ] Furthermore, prior research has not extensively examined the possible correlations between sociodemographic factors and the extent of knowledge, attitudes, and preventive practices in this particular context.…”
Section: Introductionmentioning
confidence: 99%